Alteration of the gut microbiota profile in children with autism spectrum disorder in China - Li, Hui; Guo, Wei; Li, Sijie; Sun, Bishao; Li, Ningshan; Xie, Dongjing; Dong, Zongming; Luo, Dan; Chen, Wei; Fu, Weihua; Zheng, Ji; Zhu, Jingzhen (Frontiers in Microbiology, 2024)
Autism spectrum disorder (ASD) is associated with alterations in the gut microbiome. However, there are few studies on gut microbiota of children with ASD in China, and there is a lack of consensus on the changes of bacterial species. To address this issue, we conducted a study with 1118 sample (957 ASD, 161 health children (HC)) to identify the taxonomic composition and evaluate the changes in the gut microbiota of Chinese children with ASD. We used 16S rRNA sequencing to analyze ASD children (2 to 12 years), HC (2 to 12 years). Our findings showed that the α-diversity, composition, and relative abundance of gut microbiota in the ASD group were significantly different from those in the HC groups. Compared with the HC group, the α-diversity in the ASD group was significantly decreased. At the genus level, the relative abundance of g_Faecalibacterium, g_Blautia, g_Eubacterium_eligens_group, g_Parasutterella, g_Lachnospiraceae_NK4A136_group and g_Veillonella in ASD group was significantly increased than that in HC groups, while the relative abundance of g_Prevotella 9 and g_Agathobacter was significantly decreased than that in HC groups. In addition, KEGG pathway analysis showed that the microbial functional abnormalities in ASD patients were mainly concentrated in metabolic pathways related to fatty acid, amino acid metabolism and aromatic compound metabolism, and were partially involved in neurotransmitter metabolism. This study revealed the characteristics of gut microbiota of Chinese children with ASD and provided further evidence of gut microbial dysbiosis in ASD.